Phase behavior of synthetic amphiphile vesicles investigated by calorimetry and fluorescence methods - Benatti, C. R. [UNESP]; Tiera, M. J. [UNESP]; Feitosa, E. [UNESP]; Olofsson, G. (Elsevier, 1999)
The understanding of biological membranes may be improved by investigating physical properties of vesicles from natural or synthetic amphiphiles. The application of vesicles as mimetic agents depends on the knowledgment of their structure and properties. Vesicles having different curvature and size may be obtained using different preparation protocols. We have used differential scanning calorimetry (DSC) and steady-state fluorescence to investigate the gel to liquid-crystal phase transition of vesicles prepared by sonication (SUV) and non-sonication (GUV) of the synthetic dioctadecyldimethylammonium bromide (DODAB) in aqueous solution. DSC thermograms for a non-sonicated dispersion show a well-defined pre- and main transition corresponding to two narrow peaks at 36 and 45°C in the first upscan, while in a second upscan, only the main peak was observed. The sharpness of the peaks indicate a cooperative phase behavior for GUV. For a sonicated DODAB dispersion, the first upscan shows a third peak at 40.3°C, whereas for the second upscan the peaks are not well-defined, indicating a less cooperative phase behavior. Alternatively, the fluorescence quantum yield (Φ f) and the anisotropy (r) of trans, trans, trans-1-[4-(3-carboxypropyl)-phenyl]-6-[4-butylphenyl]-1,3,5-hexatriene (4H4A) and the ratio I 1/I 3 of the first to the third vibronic peaks of the pyrene emission spectrum as function of temperature are used as well to describe the phase behavior of DODAB sonicated and non-sonicated dispersions. It is in good agreement with the DSC results that the cooperativity of the thermotropic process is diminished under sonication of the DODAB dispersion, meaning that sonication changes from homogeneous to heterogeneous populations of the amphiphile aggregates. The pre- and main transitions obtained from these techniques are in fairly good accord with results from the literature.
Keywords: Differential scanning calorimetry; Melting temperature; Steady-state fluorescence; Synthetic amphiphile vesicles; Thermotropic phase behavior